44 Minimally invasive surgical staging for early stage ovarian cancer: a long term follow up. (13th November 2020) - Gallotta, V; Conte, C; Jeong, S; Trozzi, R; Moroni, R; Scambia, G; Kim, T; Fagotti, A
Abstract : Introduction: The standard treatment for epithelial early stage ovarian cancer (eEOC) patients includes laparotomic surgical staging, according to FIGO classification. In the last decade, many investigators have assessed the safety, adequacy and feasibility of minimally invasive surgery (MIS) staging of eEOC in properly selected patients, but survival data related to different surgical approaches (open versus MIS) are extremely limited. The aim of this study is to analyze the long-term oncological outcomes in eEOC patients treated with MIS. Methods: This is a multicenter observational retrospective study conducted in two tertiary oncological centers. We selected all consecutive women (N=254) who underwent a MIS staging for clinical eEOC from January 2008 until 31st December 2016, in order to have an adequate length of median follow-up. Results: Most women had serous histotype (39.0%) and poorly differentiated tumors (53.0%). The rate of upstaged patients (final pathological FIGO stage >IIA) was 18.1%. The median duration of follow-up was 61 months (range:13–118). Eleven patients were lost to follow-up and excluded from survival analysis. Overall, 39 (16.0%) patients experienced recurrence. The 5-years disease-free survival and the 5-years overall survival rate was 84.0% and 92.5%, respectively. In the multivariate analysis the grading 1–2, FIGO stage IA-IB, and delayed surgical staging (vs. immediate staging) played a statistically significant favorable prognostic value. Conclusion: This study represents the longest follow-up of eEOC patients managed by MIS. We confirmed that MIS will continue to be a valuable therapeutic option in appropriately selected patients.